2019
DOI: 10.1159/000501821
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers to the Treatment of Chronic Hepatitis C Infection

Abstract: Background and Aims: Chronic hepatitis C (CHC) viral infection has a major impact on our health care system. The emergence of direct-acting antiviral agents (DAA) has made treatment simple (oral), efficacious, and safe. However, treatment is expensive and access is variable. Despite great treatment outcomes, only a minority of patients with CHC receive antiviral therapy. This study identifies the barriers to treatment in CHC infection. Methods: Study recruited all hepatitis C antibody-positive patients between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Several other studies have also investigated potential barriers to HCV treatment. Concerns regarding adherence of patients to both treatment and care appointments are supported by other retrospective studies of patients with CHC that have shown as many as 30-67% of patients diagnosed with CHC and not initiating treatment did so as a result of poor adherence to clinic appointments or loss to follow-up [27,37]. Similar to this study, others have also shown that advanced age [25], comorbidities (in particular psychiatric illness), as well as alcohol and drug abuse [37], can be associated with nontreatment in patients with CHC [27,28].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have also investigated potential barriers to HCV treatment. Concerns regarding adherence of patients to both treatment and care appointments are supported by other retrospective studies of patients with CHC that have shown as many as 30-67% of patients diagnosed with CHC and not initiating treatment did so as a result of poor adherence to clinic appointments or loss to follow-up [27,37]. Similar to this study, others have also shown that advanced age [25], comorbidities (in particular psychiatric illness), as well as alcohol and drug abuse [37], can be associated with nontreatment in patients with CHC [27,28].…”
Section: Plos Onementioning
confidence: 99%
“…Concerns regarding adherence of patients to both treatment and care appointments are supported by other retrospective studies of patients with CHC that have shown as many as 30-67% of patients diagnosed with CHC and not initiating treatment did so as a result of poor adherence to clinic appointments or loss to follow-up [27,37]. Similar to this study, others have also shown that advanced age [25], comorbidities (in particular psychiatric illness), as well as alcohol and drug abuse [37], can be associated with nontreatment in patients with CHC [27,28]. One recent study detailing physician attitudes towards CHC treatment in patients receiving opioid agonist treatment (OAT) in the United States, cited the perceived need for stable alcohol use and OAT, concerns regarding adherence, and challenging and marginalised patient lives as potential barriers to CHC treatment in this population [29].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014, a second generation of the DAAs have become available with a cure rate of better than 95%. Nonetheless, DAA treatment faces several challenges: (a) HCV infection can remain asymptomatic for years [ 6 ], and during this time many infections go undiagnosed while patients suffer from sustained liver damage; (b) DAA treatments do not prevent reinfections [ 7 ]; (c) DAA-resistant viruses can emerge; (d) patients with advanced liver disease remain at risk of liver cancer; and (e) HCV is highly prevalent in developing countries and among marginalized populations where access to HCV diagnosis and treatment is limited [ 8 ]. Indeed, many at-risk groups (e.g., PWIDs) spread the infection faster than they are being cured.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the release of interferon-free direct acting antiviral (DAA) therapy revolutionized HCV treatment and all DAA treatments now regularly achieve SVR rates to over 95% with few side effects [ 6 ]. However, identifying and treating individuals who do not know they are infected, poor adherence to therapy, and high therapy cost are barriers to worldwide elimination of HCV [ 7 , 8 , 9 ]. In addition, the high mutation rate of the virus may lead to the development of DAA resistance and a vaccine will be required to eliminate HCV infections worldwide [ 10 ].…”
Section: Introductionmentioning
confidence: 99%